De novo characterization of microRNAs in oriental fruit moth Grapholita molesta and selection of reference genes for normalization of microRNA expression. - Xiu Wang; Yisong Li; Jing Zhang; Qingwen Zhang; Xiaoxia Liu; Zhen Li (PLoS ONE, 2017)
MicroRNAs (miRNAs) are a group of endogenous non-coding small RNAs that have critical regulatory functions in almost all known biological processes at the post-transcriptional level in a variety of organisms. The oriental fruit moth Grapholita molesta is one of the most serious pests in orchards worldwide and threatens the production of Rosacea fruits. In this study, a de novo small RNA library constructed from mixed stages of G. molesta was sequenced through Illumina sequencing platform and a total of 536 mature miRNAs consisting of 291 conserved and 245 novel miRNAs were identified. Most of the conserved and novel miRNAs were detected with moderate abundance. The miRNAs in the same cluster normally showed correlated expressional profiles. A comparative analysis of the 79 conserved miRNA families within 31 arthropod species indicated that these miRNA families were more conserved among insects and within orders of closer phylogenetic relationships. The KEGG pathway analysis and network prediction of target genes indicated that the complex composed of miRNAs, clock genes and developmental regulation genes may play vital roles to regulate the developmental circadian rhythm of G. molesta. Furthermore, based on the sRNA library of G. molesta, suitable reference genes were selected and validated for study of miRNA transcriptional profile in G. molesta under two biotic and six abiotic experimental conditions. This study systematically documented the miRNA profile in G. molesta, which could lay a foundation for further understanding of the regulatory roles of miRNAs in the development and metabolism in this pest and might also suggest clues to the development of genetic-based techniques for agricultural pest control.